9/19/2019

# The Conclusion

I suggested a way to write a python program to come to a conclusion about the equivalence of two logical expressions. Here it is.

tv = [True,False]
# Initialize empty lists
rl = []
sl = []

# Loop through possible values of p and q
for p in tv:
for q in tv:
r = not p and not q
s = not(p or q)

# Append truth values for current p, q values
rl.append(r)
sl.append(s)

# Determine conclusion
if r == s:
conclusion = "Yes - Equivalent"
else:
conclusion = "No - Not Equivalent"

print(conclusion)
## Yes - Equivalent

# Generalization

The code above works well, but it would be better if one did not have to examine the code to see where to modify it to use different logical expressions. Could we rewrite this as a function? How can we supply the logical expressions as arguments?


def compare(f,g):

# Note that f and g are functions.

tv = [True,False]
# Initialize empty lists
rl = []
sl = []

# Loop through possible values of p and q
for p in tv:
for q in tv:
r = f(p,q)
s = g(p,q)

# Append truth values for current p, q values
rl.append(r)
sl.append(s)

# Determine conclusion
if r == s:
conclusion = "Yes - Equivalent"
else:
conclusion = "No - Not Equivalent"

return conclusion

# Exercise

Let’s try this. We need two functions which return logical values.

def f1(a,b):
compare(f1,f2)    
## 'Yes - Equivalent'